2004
DOI: 10.1103/physrevc.70.044305
|View full text |Cite
|
Sign up to set email alerts
|

Possible assignment of chiral twin bands inI188r

Abstract: High-spin states in the doubly-odd Z = 77 nucleus 188 Ir were populated in the 186 W͑ 7 Li,5n͒ reaction at 52 MeV. Two nearly degenerate ⌬I = 1 sequences with the same parity were established. Both bands have been assigned the h 9/2 i 13/2 configuration, based on the systematic behavior of these excitations in the Ir nuclei and on the measured values for the B͑M1͒ / B͑E2͒ ratios, and they are suggested as candidates for a chiral doublet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 33 publications
3
60
1
Order By: Relevance
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].Based on constrained triaxial covariant density functional theory (CDFT) calculations, it has been suggested that multiple chiral doublet (MχD) bands can exist in a single nucleus [21][22][23][24][25][26]. The theoretical prediction of MχD bands stimulated lots of experimental efforts [27][28][29][30][31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].Based on constrained triaxial covariant density functional theory (CDFT) calculations, it has been suggested that multiple chiral doublet (MχD) bands can exist in a single nucleus [21][22][23][24][25][26]. The theoretical prediction of MχD bands stimulated lots of experimental efforts [27][28][29][30][31].…”
mentioning
confidence: 99%
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Such chiral doublet bands were first identified in four N = 75 isotones in 2001 [2]. So far, many chiral candidate nuclei have been reported experimentally in the A ∼ 80, 100, 130, and 190 mass regions [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Besides the simplest chiral configurations composed of one unpaired proton and neutron, composite chiral configurations, containing more than one unpaired protons and/or neutrons, have also been observed in the odd-mass or even-even neighbors of the odd-odd chiral nuclei [10,18].…”
mentioning
confidence: 99%
“…In a recent article, Balabanski et al presented the first extensive work about the high-spin structure of the doubly odd Z = 77 nucleus 188 Ir [1]. The level scheme proposed in that work comprises two regular bands as well as a number of irregularly spaced levels of single-particle structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we wanted to carefully check the entire level scheme because some of its aspects seemed to require further clarification. One example is the fact that of the four 16 − states observed within 186 keV the highest one collects nearly all the intensity flux, whereas the yrast state of this spin is only very weakly populated [1]. 188 Ir were populated using the reaction 186 W( 7 Li, 5n).…”
Section: Introductionmentioning
confidence: 99%